2002
DOI: 10.1364/josaa.19.000197
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of the optic disc and retinal nerve fiber layer: the effects of age, optic disc area, refractive error, and gender

Abstract: We cross-sectionally examined the relationship between age, optic disc area, refraction, and gender and optic disc topography and retinal nerve fiber layer (RNFL) measurements, using optical imaging techniques. One eye from each of 155 Caucasian subjects (age range 23.0-80.8 y) without ocular pathology was included. Measurements were obtained by using the Heidelberg Retina Tomography (HRT), the GDx Nerve Fiber Analyzer, and the Optical Coherence Tomograph (OCT). The effects of age were small (R2 < 17%) and wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
73
7
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(94 citation statements)
references
References 36 publications
(58 reference statements)
10
73
7
3
Order By: Relevance
“…Sex and Disk Size-Several studies have evaluated the influence of gender on optic disk size (Table 4). 1,21,181,192 Using the CSLO, Bowd and colleagues demonstrated that optic disk area did not differ significantly between males and females (P > 0.05).21 This was supported by several other studies that measured disk size using confocal scanning laser opthalmoscopes. 1,42,109 In studies that have reported differences in disk size between genders, the differences were small.…”
Section: Race Disk Size and Glaucoma Susceptibilitymentioning
confidence: 85%
See 1 more Smart Citation
“…Sex and Disk Size-Several studies have evaluated the influence of gender on optic disk size (Table 4). 1,21,181,192 Using the CSLO, Bowd and colleagues demonstrated that optic disk area did not differ significantly between males and females (P > 0.05).21 This was supported by several other studies that measured disk size using confocal scanning laser opthalmoscopes. 1,42,109 In studies that have reported differences in disk size between genders, the differences were small.…”
Section: Race Disk Size and Glaucoma Susceptibilitymentioning
confidence: 85%
“…There is consistent evidence, regardless of the measurement technique that rim area increases with increasing disk size. 21,22,24,31,48,49,79,86,110 This raises the question, as to whether large disks have more optic nerve fibers than small disks. A larger number of nerve fibers may represent a larger anatomical reserve in various optic neuropathies including glaucoma.…”
Section: A Disk Size Neuroretinal Rim Area and Retinal Nerve Fiber mentioning
confidence: 99%
“…Además no hubo diferencia en el grosor de CFN por sexo [p = 0,532 (OD); p=0,299 (OI)] ni el tamaño del disco óptico entre hombres y mujeres, dato similar a lo encontrado por Tarannum Mansoori et al en la India (10). Al analizar el espesor de la capa de fibras nerviosas teniendo en cuenta 3 grupos etarios (40-49 años; 50-59 años; ≥60) se encontraron pequeños efectos del envejecimiento sobre este tejido, pudiéndose observar un descenso de la misma a medida que aumenta la edad, siendo mayor esta cifra en personas más jóvenes y decreciendo en personas por encima de los 60 años, aunque esta cifra no es estadísticamente significativa [(p=0,462 (OD); p=0,100 (OI)]; dato que se correlaciona con lo expuesto por Bowd et al (11) y colaboradores quienes encontraron pequeños efectos por la edad sobre la CFN consecuentemente por dicha razón laTCO se ajusta a la edad.…”
Section: Discussionunclassified
“…Rim and cup areas are significantly correlated with disc area in normal eyes, both in morphometric studies 44,45 and in HRT studies. 46,47,[55][56][57][58] This suggests that both cup area and rim area should increase their predictive value for the development of OAG by taking disc area into account.…”
Section: Discussionmentioning
confidence: 99%